Sliding abrasive wear when combining WEDM conditions and polishing treatment on H13 disks over 1045 carbon steel pins - Sánchez Egea, A. J. (2021)
Forging dies are crucial in forging to manufacture accurate workpieces. These dies are generally made of AISI H steel series and hardened and tempered medium carbon alloy steel. Dies are processed by using high-speed milling + polishing or electrical discharge machining + polishing. The surface quality of the workpiece depends on the surface properties of these dies, where surface roughness, material hardness, and wear evolution of their surfaces are critical aspects to consider. This research analyzes different wire electrical discharge machining surface conditions combined with polishing treatment to describe their influence on friction and wear. Wire electrical discharge machining defines the disks’ surface properties in finishing and roughing conditions, and polishing treatment varies in time and paper sand depending on the roughness. Abbott-Firestone curves and Rsk-Rku roughness parameters characterize the surface roughness of each studied configuration. Room temperature pin-on-disk tests were performed to analyze friction coefficients and wear rate for AISI 1045 pins and AISI H13 disks. On average, the highest (0.284) and the lowest (0.201) friction coefficients were found for the combination of finishing wire electrical discharge machining + polishing and roughing wire electrical discharge machining conditions, respectively. Scanning electron microscope images were taken to describe the wear tracks and pin degradation for different sliding abrasive configurations. The diagram correlating the surface morphology and the friction coefficient predicts the wear damage on initial surface conditions, which is crucial in the forging industry to determine tool maintenance or replacement.